Dynamic roles and intricate mechanisms of ethylene in epidermal hair development in Arabidopsis and cotton. Issue 2 (30th December 2021) - Yu, Daoqian; Li, Xiaona; Li, Yonghui; Ali, Faiza; Li, Fuguang; Wang, Zhi
Summary: Ethylene affects many aspects of plant growth and development, including root hairs and trichomes growth in Arabidopsis, as well as fiber development in cotton, though the underlying mechanism is unclear. In this article, we update the research progress associated with the main genes in ethylene biosynthesis and signaling pathway, and we propose a clear ethylene pathway based on genome‐wide identification of homologues in cotton. Expression pattern analysis using transcriptome data revealed that some candidate genes may contribute to cotton fiber development through the ethylene pathway. Moreover, we systematically summarized the effects of ethylene on the development of epidermal hair and the underlying regulatory mechanisms in Arabidopsis. Based on the knowledge of ethylene‐promoted cell differentiation, elongation, and development in different tissues or plants, we advised a possible regulatory network for cotton fiber development with ethylene as the hub. Importantly, we emphasized the roles of ethylene as an important node in regulating cotton vegetative growth, and stress resistance, and suggested utilizing multiple methods to subtly modify ethylene synthesis or signaling in a tissue or spatiotemporal‐specific manner to clarify its exact effect on architecture, adaptability of the plant, and fiber development, paving the way for basic research and genetic improvement of the cotton crop.